The H/V ratio method and its abilities in estimation of the site effects on strong ground motions in Hanoi - Tuan, Vu Minh; Vinh, Nguyen Duc; Duong, Nguyen Anh; Minh, Nguyen Sinh; Thang, Nguyen Cong; Nguyen, Pham Dinh (Vietnam Journal of Earth Sciences, 2012)
The paper presents a fundamental theory of the H/V ratio technique (or Nakamura’s method) and several obtained results in Hanoi by using this method. This is one of the most inexpensive and convenient technique to reliably estimate the fundamental resonance frequencies of soft deposits. However, the ability of the method in estimating site amplification on surface’s ground motion still remains as an open question and deserves more work to elucidate. Herein, we investigate aspects of the method at sites in Hanoi city by comparing observed H/V ratios with corresponding theoretical transfer-functions. The main goal of the study is to investigate the applicable sides of the H/V ratio method in Vietnam, and for geological conditions of Hanoi city, the H/V ratio method is a good choice for the site effect estimations.